(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This scientific article is widely covered from a scientific point of view, which states the following. Socio-political mechanisms for the prevention of modern global threats and cybersecurity in accordance with the priority areas, as well as with the goals and objectives set for the period provided for by the strategy, to develop an action plan including a set of measures in the field of information security and cybersecurity, to develop a multilateral action plan in which each measure highlights the main and other performers approved measures by type of activity, deadlines for implementation and performance indicators, successful implementation of the strategy and similar information.